2005
DOI: 10.1073/pnas.0502901102
|View full text |Cite
|
Sign up to set email alerts
|

A nicotinic acetylcholine receptor mutation conferring target-site resistance to imidacloprid inNilaparvata lugens(brown planthopper)

Abstract: Neonicotinoids, such as imidacloprid, are nicotinic acetylcholine receptor (nAChR) agonists with potent insecticidal activity. Since its introduction in the early 1990s, imidacloprid has become one of the most extensively used insecticides for both crop protection and animal health applications. As with other classes of insecticides, resistance to neonicotinoids is a significant threat and has been identified in several pest species, including the brown planthopper, Nilaparvata lugens, a major rice pest in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
384
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 390 publications
(407 citation statements)
references
References 47 publications
16
384
0
7
Order By: Relevance
“…Heterozygous N. lugens displayed a lower level of resistance, suggesting that the Y151S mutation is required in two separate nAChR genes for high level resistance to occur. 68) Correlating this observation with the findings in N. Lugens that the high and low affinity [ 3 H]-IMI binding sites contain Nlα3 and Nlα1 respectively, this suggests that a mutation in both binding sites is required to achieve high level resistance (it should be noted no investigations were performed on these insects to understand whether any non-target site alterations contributed to resistance. For example, the susceptible and resistant strains were not back-crossed to near isogenicity).…”
Section: Nachr Orthosteric Modulatorsmentioning
confidence: 93%
See 2 more Smart Citations
“…Heterozygous N. lugens displayed a lower level of resistance, suggesting that the Y151S mutation is required in two separate nAChR genes for high level resistance to occur. 68) Correlating this observation with the findings in N. Lugens that the high and low affinity [ 3 H]-IMI binding sites contain Nlα3 and Nlα1 respectively, this suggests that a mutation in both binding sites is required to achieve high level resistance (it should be noted no investigations were performed on these insects to understand whether any non-target site alterations contributed to resistance. For example, the susceptible and resistant strains were not back-crossed to near isogenicity).…”
Section: Nachr Orthosteric Modulatorsmentioning
confidence: 93%
“…More recently, the presence of dual affinity binding sites for [ 3 H]-IMI has also been observed in another hemipteran species, Nilaparvarta lugens (brown plant hopper) further solidifying the argument that hemipteran pests have two binding sites. 68,69) Certainly, not all studies on hemipteran pests have identified dual binding sites and this is likely to be down to the difficult nature of the experiments to tease out the very high affinity but low abundance site, as well as differences in interpretation of the data. 67,70) However, a general trend appears to be that when low % Triton X-100 is included in incubations the duality of binding disappears and only a single binding site (low nM K d ) is observed in aphid and fly species.…”
Section: Nachr Orthosteric Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Xenopus oocytes have been used successfully to examine nAChR subunits cloned from several invertebrate species, including the aphid Myzus persicae [89], the brown planthopper Nilaparvata lugens [90], the fruit fly Drosophila melanogaster [69,91], the locust Schistocerca gregaria [92] and the nematode Caenorhabditis elegans [93,94]. Frustratingly, the heterologous expression of invertebrate nAChRs has proved to be extremely difficult [59,95] and, in several instances, this has often been achieved only by co-expression with vertebrate nAChR subunits [65,91,96,97].…”
Section: Expression Of Recombinant Nachrs In Xenopus Oocytesmentioning
confidence: 99%
“…Hybrid nAChRs that contain both insect and vertebrate nAChR subunits have also been used extensively in an attempt to circumvent problems encountered with the inefficient heterologous 12 expression of insect nAChRs [59,95]. This approach has been adopted for studies of nAChRs cloned from insect species, including the aphid Myzus persicae [150,151], the brown planthopper Nilaparvata lugens [90,97], the cat flea Ctenocephalides felis [152] and the fruit fly Drosophila melanogaster [91,96,118,153].…”
Section: The Influence Of Subunit Compositionmentioning
confidence: 99%